THU0156 Impact of Golimumab on Physical Function and Employability of Patients with Rheumatoid Arthritis: 5-Year Data from 3 Phase III Clinical Trials. (10th June 2014) - Han, C.; Keystone, E.; Fleischmann, R.; Smolen, J.; Matteson, E.L.; Emery, P.; Genovese, M.; Gathany, T.; Hsia, E.C.
Abstract : Objectives: To assess the impact of golimumab (GLM) on physical function and employability in patients with rheumatoid arthritis (RA) with various prior treatment histories, after 5 years of therapy. Methods: The efficacy and safety of GLM were assessed in methotrexate (MTX)-naïve RA patients (GO-BEFORE, N=637), patients with inadequate response to MTX (GO-FORWARD, N=444), and patients previously treated with TNF-inhibitors (TNFi, GO-AFTER, N=445). Patients with active RA were randomized to placebo (PBO), GLM 100mg+PBO (GO-BEFORE and GO-FORWARD), or GLM (50 or 100mg), q4w. Patients in GO-BEFORE and GO-FORWARD could receive concomitant MTX or no MTX and crossed-over to GLM after wk24 (GO-FORWARD) OR wk52 (GO-BEFORE), while patients in GO-AFTER were on background (with or without) MTX and crossed-over to GLM after wk24. Clinical remission was defined as DAS28 (ESR) <2.6. Physical function was measured using Health Assessment Questionnaire (HAQ) and employability was defined as being employed or being able to work if job was available (Yes/No). 5 year data were presented by 3 patient populations. Results: At baseline, the percent of patients with disability (HAQ-DI score >0.5) in each of 3 RA populations were 90.9% in patients who were MTX-naïve, 87.6% in patients who were MTX-inadequate responders and 92.3% in patients who were TNFi-experienced. Among the analyzed patient population for employability (not retired and age<65 years), the percent of patients unemployable due to their RA at baseline were 9% in MTX-naïve patients, 8.1% in MTX-inadequate responders and 13.1% in TNF-experienced patients. After treatment with GLM, among those who had disability at baseline, 46.8% of MTX-naive patients, 37.5% of MTX-inadequate responders and 27.5% of TNFi-experienced patients had no disability (HAQ-DI score≤0.5) at wk256; among patients unemployable at baseline, 29.5% of MTX-naive patients, 28.6% of MTX-inadequate responders and 5.4% of TNFi-experienced patients regained employability at wk256. Similar trends of better outcomes on disability and employability of MTX-naïve patients were observed among those who achieved remission at wk256: 65.1% in MTX- naive patients, 54.4% in MTX-inadequate responders and 53.1% in TNFi-experienced patients achieved no disability; and 73.3% in MTX-naive patients, 50% in MTX-inadequate responders and 50.0% in TNFi-experienced patients regained employability. Conclusions: This analysis indicates that effective treatment at an early stage may result in reduction in disability and improvement in employability over the long-term. Disclosure of Interest: : C. Han Employee of: Janssen Research & Development, LLC., E. Keystone Grant/research support: Janssen Research & Development, LLC., R. Fleischmann Grant/research support: Janssen Research & Development, LLC., J. Smolen Grant/research support: Janssen Research & Development, LLC., E. Matteson: None declared, P. Emery Grant/research support: Janssen Research & Development, LLC., M. Genovese Grant/research support: Janssen Research & Development, LLC., T. Gathany Employee of: Johnson & Johnson Pharmaceutical Services, LLC, E. Hsia Employee of: Janssen Research & Development, LLC. DOI: 10.1136/annrheumdis-2014-eular.2535